Uncovering Endemism in High Montane Forests: Two New Species of Millipede Genus Tylopus Jeekel, 1968 (Diplopoda: Polydesmida: Paradoxosomatidae) from Cambodia and Laos - Srisonchai, Ruttapon; Inkhavilay, Khamla; Ngor, Peng Bun; Sutcharit, Chirasak; Likhitrakarn, Natdanai (Tropical Natural History, 2023)
Two new species of the predominantly Indochinese to southern Chinese millipedes belonging to the genus Tylopus Jeekel, 1968 are described: Tylopus bokorensis sp. nov. from southern Cambodia, and T. panhai sp. nov. from southern Laos. These species can be clearly discriminated from congeners by the shape of processes on postfemoral part of the gonopod in combination with some distinct somatic characters. Tylopus bokorensis sp. nov. is the first in this genus to be found in Cambodia. Both species inhabit montane habitats more than 1,000 m above mean sea level, and we regard them as endemic to these countries. An identification key and distribution map of Tylopus occurring in Cambodia and Laos are provided.